1,2-Alkylarylation of Activated Alkenes with Two C–H Bonds by Using Visible-Light Catalysis - Zhang, Jia-Ling; Liu, Yu; Song, Ren-Jie; Jiang, Guo-Fang; Li, Jin-Heng (Synlett, 2014)
A new visible-light promoted strategy for the difunctionalization of activated alkenes with two C–H bonds has been developed. In the presence of [Ru(bpy)3Cl2], 4-MeOC6H4N2BF4, Na2CO3 and 36 W compact fluorescent light, a variety of N-arylacrylamides underwent the 1,2-alkylarylation reaction with acetonitrile or acetone to give the corresponding functionalized oxindoles in moderate to good yields.
Keywords: alkylarylation; alkenes; acetonitrile; acetone; visible-light catalysis; oxindoles